Aerozoloterapia w praktyce zawodowej pielęgniarki pediatrycznej = Aerosolotherapy in professional practice pediatric nurse - Małecka, Bogumiła; Barczykowska, Ewa; Lewicka, Marta (Journal of Education, Health and Sport, 2016)
Małecka Bogumiła, Barczykowska Ewa, Lewicka Marta. Aerozoloterapia w praktyce zawodowej pielęgniarki pediatrycznej = Aerosolotherapy in professional practice pediatric nurse. Journal of Education, Health and Sport. 2016;6(8):67-84. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59746 http://ojs.ukw.edu.pl/index.php/johs/article/view/3732 https://pbn.nauka.gov.pl/sedno-webapp/works/741195 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Aerozoloterapia w praktyce zawodowej pielęgniarki pediatrycznej Aerosolotherapy in professional practice pediatric nurse Bogumiła Małecka1, Ewa Barczykowska2, Marta Lewicka1 1 magister pielęgniarstwa, uczestnik studiów doktoranckich na Wydziale Nauk o Zdrowiu CM w Bydgoszczy UMK w Toruniu, pielęgniarka w Wojewódzkim Szpitalu Dziecięcym im. J. Brudzińskiego w Bydgoszczy 2 doktor nauk medycznych, adiunkt w Zakładzie Pielęgniarstwa Pediatrycznego CM w Bydgoszczy UMK w Toruniu Adres do korespondencji: Bogumiła Małecka, Wojewódzki Szpital Dziecięcy im. J. Brudzińskiego w Bydgoszczy, ul. Chodkiewicza 44, Bydgoszcz, bogumila.malecka@interia.eu Streszczenie Nebulizacja jest zabiegiem leczniczym polegającym na wprowadzeniu leku do układu oddechowego w postaci aerozolu w celu działania miejscowego, jak i systemowego. Współcześnie w pneumonologii nebulizacja jest coraz częściej stosowana, jako nieagresywna metoda szybkiego dostarczenia leku w dowolny region zmienionych chorobowo dróg oddechowych. Metoda ta nie wymaga od chorego koordynacji czynności oddechowych ani wkładu wysiłkowego w fazie wdechowej i dlatego jest szeroko zastosowana w pediatrii. Celem artykułu jest przedstawienie prawidłowej techniki wykonywania zabiegu nebulizacji. Brak wiedzy odnośnie techniki zabiegu nebulizacji zarówno wśród rodziców, jak i personelu medycznego prowadzi do powstawania błędów, które mają wpływ na proces terapeutyczny . Szeroko rozumiany rozwój nauk medycznych wymusza ciągłą edukację nie tylko pracowników ochrony zdrowia, ale także pacjentów jak i ich opiekunów. Podawanie leków z wykorzystaniem aerozoloterapii jest procesem złożonym i bezwzględnie wymagana jest ścisła współpraca pomiędzy dzieckiem, rodzicami i urządzeniem w oparciu o szczegółowa wiedzę na temat prawidłowej techniki zabiegu. Słowa kluczowe: nebulizacja, dziecko, pielęgniarka pediatryczna, rodzina. Summary Nebulization is a therapeutic treatment which consists in loading the drug to the respiratory tract as an aerosol for local and systemic effects. Today in respiratory medicine nebulization is increasingly used as a non-aggressive method for the rapid delivery of the drug in any region of the affected airways. This method does not require the coordination of the patient any contribution of respiratory function of stress in the inspiration phase and is therefore widely used in pediatrics. The aim of the article is to present the proper techniques of nebulization. Lack of knowledge regarding nebulization techniques among both parents and medical personnel leads to errors that affect the therapeutic process. Widely understood development of medical science enforces continuous education not only health care workers, but as well patients and their careers. Medication administration using aerosol therapy is complex and absolutely requires close cooperation between the child, parents and device based on detailed knowledge of the proper techniques of surgery. Key words: nebulization, children, pediatric nurse, family.